Causes and Consequences of the Radicalization of Environmental Movements in Serbia - Nadić, Darko (Napredak, 2022)
The paper discusses the causes and consequences of the radicalization of environmental movements in Serbiain 2021. The causes of more radical action include several factors such as intensive economic investments sincethe beginning of this century, general distrust that political structures can solve inherited and new environmentalproblems, as well as creating a situation where environmental movements act rather like classic political movements.The paper analyzes the transformation of environmental movements and the factors that accelerated thistransformation, as well as new methods of their action, especially those caused by the case of Rio Tinto. In this regard, two new terms „politization of ecology” and „post-politization of ecology” are introduced, where politization of ecology means the use of environmental problems in short-term political promotion, while post-politization denotes the transition of environmental movements to classical political movements.
Keywords: environmental movements; environmental referendum; politization of ecology; post-politization of ecology; Rio Tinto